2008
DOI: 10.1073/pnas.0806425105
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity in marine biodiversity manipulations: Reconciling divergent evidence from field and mesocosm experiments

Abstract: Mounting concern over the loss of marine biodiversity has increased the urgency of understanding its consequences. This urgency spurred the publication of many short-term studies, which often report weak effects of diversity (species richness) driven by the presence of key species (the sampling effect). Longer-term field experiments are slowly accumulating, and they more often report strong diversity effects driven by species complementarity, calling into question the generality of earlier findings. However, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 31 publications
3
108
1
2
Order By: Relevance
“…Although we do not know if this happened in those experimental communities, it corresponds well with the complementarity effect being negative on average. A common hypothesis states that in experimental studies, namely in highly controlled laboratory experiments, monocultures often perform better than mixtures just due to the simplified environment (Duffy 2009;Powder and Cardinale 2009) or the relatively short experimental period (Cardinale et al 2007;Stachowicz et al 2008). This would even point toward a possible underestimation of diversity effects such as resource-use complementarity in mesocosm experiments, as compared with real-world ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not know if this happened in those experimental communities, it corresponds well with the complementarity effect being negative on average. A common hypothesis states that in experimental studies, namely in highly controlled laboratory experiments, monocultures often perform better than mixtures just due to the simplified environment (Duffy 2009;Powder and Cardinale 2009) or the relatively short experimental period (Cardinale et al 2007;Stachowicz et al 2008). This would even point toward a possible underestimation of diversity effects such as resource-use complementarity in mesocosm experiments, as compared with real-world ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…As the experiment of, e.g., , very elegantly shows, disturbance may dampen strong single-species effects. It is more probable that changing environmental conditions allow resource partitioning among species, and that under natural conditions, such disproportionate key species effects are greatly reduced allowing stronger diversity effects per se (Stachowicz et al, 2008). Moreover, there are many possibilities to include more organisms, species and/or trophic levels and functional groups in an extended version of our setup.…”
Section: Discussionmentioning
confidence: 99%
“…Although short-term experiments are valuable in estimating the effects of species richness and identity on ecosystem processes, they are likely to be unable to capture seasonal environmental heterogeneity and population responses. Therefore, they are likely to underestimate the influence of diversity on ecosystem processes in natural ecosystems (Stachowicz et al, 2008).…”
Section: Effects Of Species Diversity On Benthic Ecosystem Functioninmentioning
confidence: 99%
“…In 2008, they compared the effect of seaweed species richness on biomass in field plots on Pacific shores and in experimental tidal beds 9 . They found that more species meant a higher rate of biomass accumulation in the field, but not in the experimental chamber.…”
Section: Bridging the Gapmentioning
confidence: 99%